Scaffolding Talks in English Language Teaching - Rizal, Daviq (ENCOUNTER, 2012)
Scaffolding Theory was introduced in the late 1950s by JeromeBruner, a cognitive psychologist to describe childrens oral languageacquisition that was helped by their parents when they first begins tospeak. Scaffolded instruction is the systematic sequencing of promptedcontent, materials, tasks and teacherâs support to optimize Englishlearning and teaching and a process in which students are given supportuntil they can apply new skills and strategies independently and aprovision of an enabling context that provide advice, support andguidance to students. In brief, scaffolding talks is the teacherâs talk inthe language teaching. There are three kinds of scaffolding namelyfunctional, process and content. Functional scaffolding helps students tounderstand how to use or interpret the text by using tutorials,instructions and explanations of representations. Process scaffoldinghelps students to understand the path within the text. Contentscaffolding helps students to figure out an answer.